(untitled) (Research, Society and Development, 2022)
Objective: To report and reflect on the experience of occupational therapy in the process of implementing an income generation workshop with women in primary care. Methodology: This is a qualitative and descriptive study of the experience report type, which was developed through the experiences of the occupational therapist residing in the Multiprofessional Residency Program in Adult Mental Health at the Escola Superior de Ciências da Saúde. Fourteen meetings accompanied by the resident were considered for the report. Results: Through the meetings, 3 themes were selected on which extensive discussion is carried out, they are: "The solidarity economy through income generation workshops", "The practice of occupational therapy in income generation workshops" and "Women’s group and income generation.” Conclusion: It is reflected that the implementation along with the development of the actions performed in the income generation workshop, became important teaching and learning possibilities for the occupational therapist resident in mental health specialization. It is understood that the Primary Care proposal involves a change in the biomedical model focused on the disease and seeks to consolidate comprehensive care and an expanded clinic that sees the individual in a biopsychosocial logic, becoming the main characteristic of income-generating groups with women.